Value Creation on CRM: Evidence of Employee Competence in Bird’s Group Serviced Apartments in Indonesia - Irma M Nawangwulan; Josephine P. Sawirin; Samuel PD Anantadjaya (Lembaga Penelitian Universitas Pasundan, 2015)
With the fast-pace growth on apartment buildings in major cities in Indonesia, it is interesting to investigate the underlying reasons behind such high growth rates. Relying on the perspective of employee competence and prevailing activities on customer relationship management (CRM), this study intends to investigate the degree on influential factors toward organizational value creation for Bird Group, as the owner/manager of a few service apartments in the city of Bandung, in the province of Jawa Barat, Indonesia. It has become a public knowledge that any potential improvements on employee competence should generally impact the employee performance in carrying their tasks and responsibilities. Improvements on employee performance are expected to bring about enhancements on the combinations of CRM activities. The betterment in CRM activities may likely inspire public to step-up their buying intentions (BI) toward products/services. This may be true as the general level of customer satisfaction has increased. Undoubtedly, the higher BI is expected to push-up the organizational value creation. Having said that, it is uncertain whether or not such relationships do occur among those chosen variables in this study. This study relies on a quantitative approach to objectively evaluate empirical evidence. Since there are countless theoretical discussions on competence and the needs for employee training/development, this study seeks to investigate the actual significant influence of employee competence toward CRM activities, BI, customer satisfaction and organizational value creation. It is expected that the relationships among variables are positive and significant. In addition to the quantitative approach, a qualitative method is also utilized to extract managerial insights on the relationships among variables/indicators. Keywords: employee competence, CRM, customer satisfaction, buying intention, organizational value creation